2022
DOI: 10.1093/heapro/daac018
|View full text |Cite
|
Sign up to set email alerts
|

Activate Your Health: impact of a real-life programme promoting healthy lifestyle habits in Canadian workers

Abstract: Summary The workplace has been suggested as a good setting for the promotion of healthy lifestyles. This article examines the impact of Activate Your Health programme, provided over an average of 1.35 years, on employee health and lifestyle habits (actual and intention to improve). Companies selected one of the programme’s four options (number of interventions in parentheses): Control (2), Light (8), Moderate (13) and High (14). Employees (n = 524) completed an online questionnaire at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Similar results were found in a study of pregnant and puerperal women in Peruvian communities with complete secondary education, who considered the use of rubber gloves as an excellent preventive measure, while they considered the use of homemade masks as an incorrect preventive measure; these results were positive thanks to the correct information provided by the health establishment in their community [ 20 ]. Likewise, Kugathasan et al showed that Canadian workers had a good knowledge of preventive measures against COVID-19; these results were thanks to the health information given by television programs, radio, press, and social networks [ 3 ]. On the other hand, in the Colombian population, it was shown that the female population had better preventive practices against SARS-CoV-2 infection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in a study of pregnant and puerperal women in Peruvian communities with complete secondary education, who considered the use of rubber gloves as an excellent preventive measure, while they considered the use of homemade masks as an incorrect preventive measure; these results were positive thanks to the correct information provided by the health establishment in their community [ 20 ]. Likewise, Kugathasan et al showed that Canadian workers had a good knowledge of preventive measures against COVID-19; these results were thanks to the health information given by television programs, radio, press, and social networks [ 3 ]. On the other hand, in the Colombian population, it was shown that the female population had better preventive practices against SARS-CoV-2 infection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an extended range of behaviors influences human health, such as smoking, alcoholism, and drug use [ 2 ]. Lifestyles are vital in reducing all-cause mortality, maintaining health and well-being, and have also been shown to affect the prevention of various diseases positively [ 3 ]. On the other hand, certain lifestyle behaviors have been shown to predict the presence of depression and anxiety, psychiatric symptoms whose prevalence has increased during the coronavirus disease 2019 (COVID-19) pandemic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%